Coconuts and curtain cakes: The production of wh-questions in ASD. (February 2021) - Sukenik, Nufar; Morin, Eléonore; Friedmann, Naama; Prevost, Philippe; Tuller, Laurice
Background and aims: Children with autism spectrum disorders (ASD) have been found to exhibit difficulties in wh -question production. It is unclear whether these difficulties are pragmatic or syntactic in nature. The current study used a question elicitation task to assess the production of subject and object wh -questions of children with ASD in two different languages (Hebrew and French) wherein the syntactic structure of wh -questions is different, a fact that may contribute to better understanding of the underlying deficits affecting wh -question production. Crucially, beyond the general correct/error rate we also performed an in-depth analysis of error types, comparing syntactic to pragmatic errors and comparing the distribution of errors in the ASD group to that of children with typical development (TD) and children with Developmental Language Disorder (DLD). Results: Correct production rates were found to be similar for the ASD and DLD groups, but error analysis revealed important differences between the ASD groups in the two languages and the DLD group. The Hebrew- and French ASD groups were found to produce pragmatic errors, which were not found in children with DLD. The pragmatic errors were similar in the two ASD groups. Syntactic errors were affected by the structure of each language. Conclusions: Our results have shown that although the two ASD groups come from different countries and speak different languages, the correct production rates and more importantly, the error types were very similar in the two ASD groups, and very different compared to TD children and children with DLD. Implications: Our results highlight the importance of creating research tasks that test different linguistic functions independently and strengthen the need for conducting fine-grained error analysis to differentiate between groups and gain insights into the deficits underlying each of them.